Studie av energianvändningen på Spira förskola : En jämförande studie av faktiskt och simulerad energianvändning samt en parameterstudie av ingående data vid simuleringar av energianvändning - Larsson, Anton (2014)
In this thesis the actual and simulated energy use at Spira preschool in Luleå was investigated. The actual specific corrected energy use was determined to 121.4 kWh/m2 and year. Before the preschool was constructed an estimation of the specific energy use was conducted using the simulation software VIP-Energy where the energy use was determined to 78.5 kWh/m2 and year. Thus the actual usage exceeded the simulated one with 54.6 %.A parameter study was also conducted where the inputs to the simulation software was examined. The intention was to determine the total change in energy use when input data was changed. The following parameters where included in the study;• Operating time of the ventilation system• Horizon Angle• Indoor temperature• Climate Zone• Ratio between supply and exhaust air• Air exchange rate for the ventilation system• Reflection of sun from surrounding lands• Thermal efficiency of the heat exchanger in the ventilation system• Wind Speed• Rotation of the buildingKey numbers that could be used to quickly estimate the impact on total energy use has also been compiled for the majority of the studied parameters. In all cases a high degree of explanation was obtained when the relationship between input- and output data was estimated.For example, when the operating time of the ventilation system was extended by 1 hour per weekday the total energy consumption increased by 2.85 kWh/m2 and year. When the indoor temperature was increased by 1°C the energy use increased by 4.42 kWh/m2 year. When the air exchange rate was increased by 0.1 l/s m2 the total energy use increased by 1.88 kWh/m2 and year. The thermal efficiency of the heat exchanger in the ventilation system also had a great impact in the model where energy use decreases by 0.97 kWh/m2 and year for every percentage increase in recovery rate. The Horizon angle, sun reflection from the surroundings, wind speed and rotation of the building had a limited impact on the total energy use. Validerat; 20140329 (global_studentproject_submitter)